School and individual‐level characteristics are associated with children's moderate to vigorous‐intensity physical activity during school recess - Karen Martin; Alexandra Bremner; Jo Salmon; Michael Rosenberg; Billie Giles‐Corti (Elsevier, 2012)
Abstract Objective: The objective of this study was to identify school environmental characteristics associated with moderate to vigorous physical activity during school recess, including morning and lunch breaks. Methods: Accelerometry data, child‐level characteristics and school physical activity, policy and socio‐cultural data were collected from 408 sixth grade children (mean age 11 years) attending 27 metropolitan primary schools in Perth, Western Australia. Hierarchical modelling identified key characteristics associated with children's recess moderate to vigorous physical activity (RMVPA). Results: Nearly 40% of variability in children's RMVPA was explained by school environment and individual characteristics identified in this study. Children's higher daily RMVPA was associated with newer schools, schools with a higher number of grassed surfaces per child and fewer shaded grassed surfaces, and the physical education coordinator meeting Australian physical activity guidelines. Conclusions: Characteristics of the school physical and social environments are strongly correlated with children's MPVA during recess. Implications: The school environment is an ideal target for maximising children's physical activity during recess. Future research could examine the impact of modifying these environmental characteristics on children's school physical activity.